Rancang Bangun Aplikasi Pengendalian Inventori Menggunakan Metode Economic Order Quantity (EOQ) Pada Klinik H2LC Surabaya - Tukloy, Eka Putri D; Indah K, Weny; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
H2LC clinic is a clinic Aesthetic & Anti Aging berkonsisten apply the concept of healthy living by combining elements of beauty and health of the skin and body. Clinic H2LC presenting beauty products from the best herbal ingredients and are safe to use in the long term. H2LC clinic is located at Jl Raya Ngagel Jaya Utara No. 71, Surabaya. Business processes H2LC include Care Clinic, Consultation, and Beauty Products. At this time the business process at Beauty Clinic H2LC not computerized, so that the customer data collection process, data collection product, supplier data collection, sales transactions, purchases and sales summary along with any purchase requires a long time. Because the sales department must seek customer data one by one on the shelves available, sales should check the remaining products are available manually and record sales transactions manually memorandum cause difficulties in clinical H2LC merekap sales reports. Section pharmacist experienced difficulties in checking the stock of products available or empty and had trouble buying a recapitulation report. H2LC clinics often mangalami emptiness products that cause customer clinics H2LC not satisfied due to existing products are often empty and requires a long time to order these products. Therefore, in this final project made an inventory control application using methods Ecomomic Order .Quantity (EOQ) in Surabaya H2LC Clinic. Applications Inventory Control Method Using EOQ can set the number of product inventory, in order to produce the amount of products supplied is not too much or not too little (empty)